Remote sensing of suspended sediment over Gulf of Martaban - Mustafa, Mamat; Abd Rahman, Matamin; Fadhli, Ahmad (2015)
Gulf of Martaban is located at the north of Andaman, and is one of the world most turbid areas. e presence of suspended sediment concentration (SSC) in the water body could reduce the underwater transmittance. is study has been conducted to investigate the variation of SSC over the Gulf of Martaban. Remote sensing reectance (Rrs) of 667 nm is used as a proxy to represent the sediment SSC variation over the study area. e data for the period of July 2002 to March 2014 acquired from MODIS Aqua 4 km resolution are used in this study. As a result, there is no obvious yearly variation in the SSC cover area. e SSC variation over this study area is found to be sea-sonal. High homogenous SSC covers area observably during the northeast (NE) monsoon season that occurs from December to January. e sediment cover area could reach the latitude of 15°N that located at the south of the gulf. During southwest (SW) monsoon season that occurs from May to September, low and sparse SSC cover area is observed. As a consequence, the area covered by the SSC is higher during the NE monsoon season as compared to the SW monsoon season. Hence, the SSC cover area during the NE monsoon season is greater than the yearly averaged SSC cover area. Meanwhile the SSC cover area during the rainy SW monsoon season is less than the yearly and NE monsoon season.